Histone post-translational modification and heterochromatin alterations in neurodegeneration: revealing novel disease pathways and potential therapeutics - Fisher, Raven M. A.; Torrente, Mariana P. (Frontiers in Molecular Neuroscience, 2024)
Alzheimer’s disease (AD), Parkinson’s disease (PD), Frontotemporal Dementia (FTD), and Amyotrophic lateral sclerosis (ALS) are complex and fatal neurodegenerative diseases. While current treatments for these diseases do alleviate some symptoms, there is an imperative need for novel treatments able to stop their progression. For all of these ailments, most cases occur sporadically and have no known genetic cause. Only a small percentage of patients bear known mutations which occur in a multitude of genes. Hence, it is clear that genetic factors alone do not explain disease occurrence. Chromatin, a DNA-histone complex whose basic unit is the nucleosome, is divided into euchromatin, an open form accessible to the transcriptional machinery, and heterochromatin, which is closed and transcriptionally inactive. Protruding out of the nucleosome, histone tails undergo post-translational modifications (PTMs) including methylation, acetylation, and phosphorylation which occur at specific residues and are connected to different chromatin structural states and regulate access to transcriptional machinery. Epigenetic mechanisms, including histone PTMs and changes in chromatin structure, could help explain neurodegenerative disease processes and illuminate novel treatment targets. Recent research has revealed that changes in histone PTMs and heterochromatin loss or gain are connected to neurodegeneration. Here, we review evidence for epigenetic changes occurring in AD, PD, and FTD/ALS. We focus specifically on alterations in the histone PTMs landscape, changes in the expression of histone modifying enzymes and chromatin remodelers as well as the consequences of these changes in heterochromatin structure. We also highlight the potential for epigenetic therapies in neurodegenerative disease treatment. Given their reversibility and pharmacological accessibility, epigenetic mechanisms provide a promising avenue for novel treatments. Altogether, these findings underscore the need for thorough characterization of epigenetic mechanisms and chromatin structure in neurodegeneration.